Active plasmonic nanodevices: From basic principles to emerging applications - Chi Zhang; Tao Ding (Responsive Materials)
Abstract Tunable plasmonics has shown a wide range of applications in (bio)chemical sensing, displays, actuators, photonic chips, biomedicine, etc. in the last 2 decades. This review focuses on their recent development from the device perspective, which involves the understanding of fundamental principles and specific applications with desired functionality and compatibility. We classify these active plasmonic devices based on the nature of their structures and working environment as colloidal‐based, chip‐based, and colloidal chip‐based to further elaborate their performance and functions. We also highlight recent progress on tunable surface‐enhanced Raman spectroscopy, metasurfaces, and chiroptics to show the emerging applications of tunable plasmonic systems. We conclude this review with a general perception of the research trend in this field and challenges for their practical applications.